2016
DOI: 10.1016/j.cmi.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Anal human papillomavirus in HIV-uninfected men who have sex with men: incidence and clearance rates, duration of infection, and risk factors

Abstract: Little is known regarding the natural history of anal human papillomavirus (HPV) infection. We aimed to evaluate incidence and clearance rates, their risk factors, and duration of anal HPV infection in HIV-uninfected men who have sex with men (MSM). A longitudinal study was conducted. Anal samples were analysed using the Linear Array HPV Genotyping test. Incidence and clearance rates, and corresponding risk factors, were estimated using a two-state Markov model. Overall, 155 MSM (median age 33.4 years) attendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 28 publications
11
31
1
Order By: Relevance
“…The incidence and clearance of male PA HPV infection among heterosexual men in our study were similar with the data from men who have sex with women in the HPV in men (HIM) study, 29 whereas a much higher incidence and lower clearance were found in men who have sex with men, [29][30][31] HIV-infected men 6,32 and HIV-infected men who have sex with men. Therefore, we cannot verify the proportion of populations with different sexual behaviors in the total population.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The incidence and clearance of male PA HPV infection among heterosexual men in our study were similar with the data from men who have sex with women in the HPV in men (HIM) study, 29 whereas a much higher incidence and lower clearance were found in men who have sex with men, [29][30][31] HIV-infected men 6,32 and HIV-infected men who have sex with men. Therefore, we cannot verify the proportion of populations with different sexual behaviors in the total population.…”
Section: Discussionsupporting
confidence: 87%
“…We calculated the cumulative prevalence, incidence rates and clearance rates for type-specific HPV and grouped HPV types as follows: any HPV types; any oncogenic HPV types (16,18,31,33,35,45,51,52,56,58, 59 and 68) 18 ; any nine-valent vaccine HPV types (9v; 6,11,16,18,31,33,45, 52 and 58); HPV 16/18 and HPV 6/11. We calculated the cumulative prevalence, incidence rates and clearance rates for type-specific HPV and grouped HPV types as follows: any HPV types; any oncogenic HPV types (16,18,31,33,35,45,51,52,56,58, 59 and 68) 18 ; any nine-valent vaccine HPV types (9v; 6,11,16,18,31,33,45, 52 and 58); HPV 16/18 and HPV 6/11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,24,[29][30][31] HPV-16 appeared to be the most prevalent genotype in both study groups, and this might be explained by the high incidence and long persistence of this genotype in anal infections, as shown by longitudinal studies. [32][33][34] As expected, we observed that the prevalence of HR types significantly increased with the severity of the cytological findings in both populations. All individuals with an HSIL harbored an HR HPV infection with the exception of 1 HIV-infected patient who was positive for possibly carcinogenic HPV-53.…”
Section: Cancer Cytopathologysupporting
confidence: 87%
“…HPV uptake was associated with a history of genital warts and higher number of male partners after adjusting for other potential confounding factors. While it is not yet known what coverage of MSM would be required to achieve the same dramatic declines achieved in heterosexuals, it has been suggested it needs to be at least as high as heterosexuals based on the higher rate of partner change,10 and the potentially greater and longer duration of infectiousness at the anus 16. These factors, combined with the rapid acquisition of HPV in young MSM and high rates of partner change before vaccination, suggest that a 42% coverage will not be sufficient to see dramatic declines in HPV and substantial herd protection.…”
Section: Discussionmentioning
confidence: 99%